Bridging the age gap: a review of molecularly informed treatments for glioma in adolescents and young adults - Weiser, Annette; Sanchez Bergman, Astrid; Machaalani, Charbel; Bennett, Julie; Roth, Patrick; Reimann, Regina R.; Nazarian, Javad; Guerreiro Stucklin, Ana S. (Frontiers in Oncology, 2023)
Gliomas are the most common primary central nervous system (CNS) tumors and a major cause of cancer-related mortality in children (age <15 years), adolescents and young adults (AYA, ages 15-39 years), and adults (age >39 years). Molecular pathology has helped enhance the characterization of these tumors, revealing a heterogeneous and ever more complex group of malignancies. Recent molecular analyses have led to an increased appreciation of common genomic alterations prevalent across all ages. The 2021 World Health Organization (WHO) CNS tumor classification, 5th edition (WHO CNS5) brings forward a nomenclature distinguishing "pediatric-type" and "adult-type" gliomas. The spectrum of gliomas in AYA comprises both "pediatriclike" and "adult-like" tumor entities but remains ill-defined. With fragmentation of clinical management between pediatric and adult centers, AYAs face challenges related to gaps in medical care, lower rates of enrollment in clinical trials and additional psychosocial and economic challenges. This calls for a rethinking of diagnostic and therapeutic approaches, to improve access to appropriate testing and potentially beneficial treatments to patients of all ages.